PENERAPAN PERILAKU KELUARGA SADAR GIZI (KADARZI) DAN STATUS GIZI BALITA USIA 24-59 BULAN DI PUSKESMAS KRANJI BEKASI - Oktaviani, Putri Pratiwi; Djafar, Meylina; Fayasari, Adhila (Universitas Islam Negeri Walisongo Semarang, 2019)
This study aimed to analyze association between the implementation of nutrition conscious family with the nutritional status of children aged 24-59 months in Puskesmas Kranji Bekasi. This research used a cross sectional design. Subjects were 71 mothers who had children aged 24-59 months taken by purposive sampling. Weight and height data were measured by stepping scales and microtoise, then converted to z-scores. Bivariate analysis using Chi-Square test. Underweight about 9 (12,7%) subjects, and 42 (59,2%) families did not apply KADARZI, indicator points that have not been done includes providing nutritional supplements (vitamin A) (7 %), varied meals (14,1%), using iodized salt (16,9%), weighing regularly (19,7%), and giving exclusive breastfeeding 31 (43,7%). Based on Chi-Square test is proved that there is correlation between KADARZI implementation with nutritional status of children aged 24-59 months. The implementation of KADARZI had a significant association between nutritional status of children aged 24-59 months (p-value 0,006), particularly at indicators irregularly posyandu participation.